Gendered labor markets and capitalist accumulation. Issue 1 (2nd October 2018) - Ghosh, Jayati
Abstract: Gender relations affect economic processes, especially macroeconomic patterns and accumulation trajectories, so capitalism relies on gender construction of societies to further its expansion. For example, changes in women's involvement in paid and unpaid work impact the extent to which the unpaid care economy subsidizes the formal economy. Failure to recognize this leads to misleading estimates of aggregate labor productivity and its change over time. Similarly, ignoring the gender distribution of cross-border migration can lead to wrong expectations about the patterns of remittance flows during business cycles in the host country.